If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 4y = 13 Solving 6x + 4y = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 6x + 4y + -4y = 13 + -4y Combine like terms: 4y + -4y = 0 6x + 0 = 13 + -4y 6x = 13 + -4y Divide each side by '6'. x = 2.166666667 + -0.6666666667y Simplifying x = 2.166666667 + -0.6666666667y
| -92=4+8x | | x+23[2/11]=25 | | 12+1/5m=20 | | 6t+5/9t-5=2t+7/3t-7 | | 6x+4(x-3)=13 | | 92x=883.2 | | 2X-6=3X+7 | | x=150+0.85(x) | | w-147.67=144.67 | | 3/5x21=3x | | .3333p+7=12-.6666p | | (2x^2)/(0.8-x^2)=53.3 | | 3/5+3=21x | | z/325=7 | | z/23=6 | | 1/9p=5/6 | | x=200+0.8(x) | | -5(X-4)+8X=6X-2 | | -6y-9=-3(y+9) | | x+65=50+75 | | 10/27=5/9t | | z^23=6 | | 18y-6=8y-70 | | 50+75=x+65 | | 5(X+4)/6=2X-5 | | 0.2x+1-2=0.5 | | x+(.01x)=15000 | | D=7/3(m-76) | | 2x/2-3x-1=0 | | 5x-3/2+6=-11 | | x-(0.01*x)=1500 | | -7-35/8 |